Development of readout electronics for the RICH detector in the HADES and CBM experiments - HADES RICH upgrade, mRICH detector construction and analysis - - Weber, Adrian Amatus; Justus Liebig University Giessen (My University, 2021)
This work contributes large parts to the development, installation and monitoring of the FPGA based readout of the new DiRICH board in the HADES, CBM and mCBM experiments. In addition, an analysis of data taken in the 2020 mCBM beamtime campaign is performed. The HADES and CBM experiments are fixed target heavy ion experiments at the GSI Helmholtz Centre for Heavy Ion Research in Darmstadt/Germany respectively at the upcoming Facility of Antiproton and Ion Research (FAIR). HADES is a well established experiment at the SIS18 accelerator of GSI and will be completing the future Compressed Baryonic Matter (CBM) pillar of FAIR together with the CBM experiment at SIS100. Both experiments aim for the measurement of di-electrons and their spectrum in different energy regimes. The Ring Imaging Cherenkov (RICH) detector, a subdetector in both experiments, is allowing for clean electron identification. The HADES RICH detector has been upgraded with a new photon detector based on MAPMTs. New front end electronics have been developed which will also be used for CBM at SIS100. The DiRICH FEE is based on TDC measurement of MAPMT signals in a FPGA on the DiRICH board. The presented work focusses on the upgrade of the HADES RICH with a new photodetection plane based on MAPMTs and DiRICH readout. The use of 428 MAPMTs with 856 DiRICH boards is opening up new capabilities in the electron identification for the HADES experiment and is in parallel a large scale prototype test of the CBM RICH detector electronics. The powering scheme as well as the monitoring of the RICH is upgraded to match the new electronics. The full upgraded HADES RICH performed excellently in the march 2019 Ag+Ag beamtime at 1.58 AGeV. A second prototype, based on the same DiRICH electronics as the upgraded HADES RICH, has been developed for the mCBM experiment. The mCBM experiment is a prototype experiment of the future CBM experiment for the test of the common free-streaming readout and online analysis algorithms. A dedicated mRICH prototype has been designed, constructed and commissioned with a new readout concept, based on the known TrbNet network and adapted to the free-streaming environment. The readout concept of mRICH in phase-I of mCBM is further developed towards phase-II with the first implementation of the readout concept on the final CBM hardware. The new development includes i.a. major changes in the data transport and the handling of the readout. The data from the phase-I beamtime 2020 of mCBM is analysed in terms of the readout performance as well as the synchronisation to the other sub-detectors. Excellent time- and spatial correlations between the mRICH and mTOF detectors are found and described in detail in this work. An additional analysis of the mRICH rings and the hits is performed in detail and shows the reliable behaviour of the constructed mRICH prototype detector in the free streaming environment. Finally, in a first test beam, a first version of the phase-II readout with full synchronisation to the other mCBM detectors could successfully be brought into operation.
Keywords: CBM; HADES; TRB; FPGA; mRICH; mCBM; RICH; FEE; DiRICH; DAQ; analysis; ddc:530